THE STRATEGY, ORGANIZATION, AND PROGRESS OF THE HUPO HUMAN PROTEOME PROJECT - Omenn, Gilbert S. (2013)
The Human Proteome Project is a major, comprehensive initiative of the Human Proteome Organization. This global collaborative effort aims to identify and characterize at least one protein product and many PTM, SAP, and splice variant isoforms from the 20,300 human protein-coding genes. The deliverables are an extensive parts list and an array of technology platforms, reagents, spectral libraries, and linked knowledge bases that advance the field and facilitate the use of proteomics by a much wider community of life scientists. Such enablement will help address the Grand Challenge of using proteomics to bridge major gaps between evidence of genomic variation and diverse phenotypes.